Data of how morally ‘loaded’ labels in the built environment influence social judgments and perceptions of comfort and visibility - Haga, Andreas (University of Gävle, 2024)
Forty-four individuals were presented with 16 different images of faces under a desk lamp.

The experiment consisted of three phases:

1. First, the participants rated how well they could see the person in front of them (scale: 1 = not at all well, 11 = very well).

2. They were then asked to evaluate various personality traits for each face under two different lamps. The personality traits were as follows: how irresponsible, selfish, environmentally friendly, cold, dishonest, wasteful, ruthless, or uninterested the person appeared to be. This was rated on a scale from 1 to 6, with dichotomous endpoints (e.g., 1 = cold, 6 = warm).

3. After all personality evaluations, a final assessment was made regarding how comfortable it was to work under the lamp’s light (scale: 1 = not at all comfortable, 11 = very comfortable).

All evaluations were conducted under the same desk lamp. However, for half of the image evaluations, participants were told that the lamp was environmentally friendly, while for the other half, they were told it was a conventional incandescent lamp. This information was provided both verbally and via a label attached to the lamp’s base. The order of the lamp conditions was counterbalanced, meaning each image was assessed under both conditions.

The three phases were repeated 16 times (16 images).

After all the evaluations, participants completed two questionnaires: one on environmental concern (Environmental Concern; EC) and one on values (Value Orientation Scale; VOS).

The environmental concern questionnaire was structured as follows:
“How concerned are you that today’s ENVIRONMENTAL PROBLEMS will affect…?” Circle the option for each statement that best matches your view. (1 = Not at all concerned, 7 = Very concerned)
All living beings; Me; All humans; Plants; My lifestyle; People close to me; Animals; My health; Future generations; Marine life; My future; My children

The values questionnaire was structured as follows:
“Imagine that these 13 values are your guiding principles in life. We ask you to rate how important each one is to you personally. Circle the option that best matches your view. (1 = Completely opposed to my principles, up to 7 = Extremely important)”

Take your time to think through your evaluations before responding.

Social status; Equality; Respect for our Earth; Wealth; A world at peace; Being one with nature; Power; Social justice; Protecting our nature; Being influential; Being helpful; Preventing pollution; Being ambitious

Three different indexes could be created for both questionnaires: an egoistic, an altruistic, and a biospheric index. To remove shared variance and isolate unique concern for each index, the mean of all scale items was subtracted from the three EC indexes and the VOS indexes.

Then, the adjusted indices for all environmental concern dimensions were combined with the adjusted indices for all value dimensions. This was done to obtain a highly reliable measure of the three main attitude dimensions. More specifically, an average was calculated for the two altruistic dimensions, the two biospheric dimensions, and the two egoistic dimensions to create three more general indices for altruistic orientation, biospheric orientation, and egoistic orientation.

The dataset includes three difference variables that measure: (1) The difference in perceived comfortableness between the lamp marked as conventional and the one marked as environmentally friendly. (2) The difference in perceived visibility between the lamp marked as conventional and the one marked as environmentally friendly. (3) The difference in perceived personality traits between the lamp marked as conventional and the one marked as environmentally friendly.

Fyrtiofyra personer har blivit presenterade av 16 olika bilder på ansikten under en bordslampa.

Experimentet bestod av tre faser:

1. Först svarade personerna hur väl de såg personen framför dem (skala 1 inte alls bra – 11 väldigt bra).

2. De blev ombedd att skatta olika personlighetsdrag för varje ansikte under två olika lampor. Personlighetsdragen var följande: hur oansvarig; självisk; miljövänlig; kall; oärlig; slösaktig; hänsynslös; ointresserad personen såg ut att vara. Detta gjordes på en skala från 1 till 6, med diktotoma slutpunkter (exempelvis 1 kall – 6 varm).

3. Efter alla personlighetsskattningar gjordes en sista bedömning, hur behagligt det hade varit att jobba under lampans ljus (skala 1 inte alls behagligt – 11 väldigt behagligt).

Samtliga skattningar gjordes under samma bordslampa. Men under hälften av skattningarna av bilderna sades det att lampan var miljövänlig, medan för den andra hälften sades det att lampan var en vanlig glödlampa. De fick informationen muntligt men också av en etikett som sattes fast vid lampfoten. Ordningen på lampbetingelserna var motbalanserad, det vill säga att varje bild bedömdes under båda betingelserna.

De tre faserna upprepades 16 gånger (16 bilder).

Efter alla bedömningar svarade försöksdeltagarna på två enkäter en för miljöomsorg (Environmental Concern; EC) och en för värderingar (Value Orientation Scale; VOS).

Enkäten miljöomsorg hade denna utformning:

Hur bekymrad är du för att dagens MILJÖPROBLEM drabbar…?. Ringa in det alternativ för varje påstående som stämmer bäst med din uppfattning. (1 = Inte alls bekymrad, 7 = Mycket bekymrad)
Alla levande varelser; Mig; Alla människor; Växter; Min livsstil; Människor i min närhet; Djur; Min hälsa; Framtida generationer; Livet i havet; Min framtid; Mina barn

Enkäten för värderingar hade denna utformning:

Tänk dig att dessa 13 värderingar är Dina vägledande principer i livet. Vi ber Dig att bedöma hur viktig var och en är för just Dig. Ringa in det alternativ som stämmer bäst med din uppfattning. (1 = Helt i motsats till mina principer, och så vidare till 7 = Extremt viktigt)

Tänk igenom dina bedömningar noga innan du svarar.

Social status; Jämlikhet; Respektera vår jord; Rikedom; En värld i fred; Vara ett med naturen; Makt; Social rättvisa; Skydda vår natur; Vara inflytelserik; Vara hjälpsam; Förhindra föroreningar; Vara ambitiös

Tre olika index kunde skapas för båda enkäterna. Ett egoistiskt, ett altruistiskt och ett biosfäriskt. För att plocka bort den gemensamma variansen för att få fram den unika oron för varje index subtraherades medelvärdet för samtliga skal-items från de tre EC-indexen och VOS-indexen.

Sedan slogs de justerade indexen för samtliga miljöomsorgsdimensioner ihop med de justerade indexen för samtliga värderingsdimensioner. Detta gjordes för att få ett mycket tillförlitligt mått på de tre huvudsakliga attityddimensionerna. Mer specifikt det togs fram ett medelvärde för de två altruistiska dimensionerna, de två biosfäriska dimensionerna och de två egoistiska dimensionerna för att få tre mer allmänna index för altruistisk orientering, biosfärisk orientering och egoistisk orientering.

Det finns tre diff-variabler i datasetet som är måtten på (1) skillnaden mellan skattad behaglighet under den vanliga och den miljövänliga märkta lampan, (2) skillnaden mellan skattad synlighet under den vanliga och den miljövänliga märkta lampan, och (3) skillnaden mellan skattade personlighetsdrag under den vanliga och den miljövänliga märkta lampan.
Data om hur moraliskt 'laddade' benämningar i den byggda miljön påverkar sociala bedömningar samt uppfattningar av komfort och synlighet
Keywords: INTERPERSONAL RELATIONS; MELLANMÄNSKLIG RELATION; CONSUMER INFORMATION; KONSUMENTINFORMATION; ELECTRIC LIGHTING; ELEKTRISK BELYSNING; MORAL BEHAVIOUR; MORALISKT BETEENDE; CLIMATE CHANGE; KLIMATFÖRÄNDRINGAR; judgement of character; människokännedom; ENVIRONMENTAL AWARENESS; MILJÖMEDVETENHET; PSYCHOLOGY; PSYKOLOGI; Psychology; Psykologi